SISTEM PENDUKUNG KEPUTUSAN PEMBELIAN LATEKS PETANI PADA PT HEVEA ANUGRAH NATURA - Kelvin Verdian; Yulistia Yulistia (DIBINOM : Digital Business, Economic Jurnal, 2025)
The purpose of developing this system at PT HEVEA ANUGRAH NATURA is to be able to assist Head Operations in determining the best latex quality for sub-region farmers effectively and efficiently. The methodology used in developing this system is iteration which has four stages, namely the planning phase, analysis phase, design phase and implementation phase. In this decision support system the methodology used is Multi-Attribute Utility Theory (MAUT). The system created will use Visual Studio Code, be website based, PHP programming language and use MySql database storage. In this way, the authot will help solve existing problems by building a Decision Support System for Farmer’s Latex Purchasing at PT HEVEA ANUGRAH NATURA